PENYULUHAN TENTANG PEMANFAATAN DAUN BANGUN-BANGUN (COLEUS AMBOINICUS LOUR.) TERHADAP PENINGKATAN PRODUKSI ASI - Septa Dwi Insani; Dewi Novika Manullang; Eka Sri Wahyuni; Husna Sari; Siti Marlina; Lili Suryani Tumanggor (INSTITUT KESEHATAN DELI HUSADA, 2021)
A systematic analysis of non-communicable diseases (NCD) risk factors, globally in 21 countries in 1999-2010, showed that not optimal of breastfeeding was one of the risk factors contributing to the development of NCD. According to research reported that limited of milk production is the main reason for mother’s not giving exclusive breastfeeding to the infant. As an alternative solution to treat these problems, used galactopoetics herbs are highly recommended. The medicinal-herb interactions associated with galactagogues have concrete evidence, but the evidence explaining the mechanism of action of herbs as galactagogues is still very limited and scares. One of the pharmacological-used plants has been used as galactagogues, is Coleus amboinicus Lour. In vivo studies using animals and human experiments showed that this plant had anti-diabetic activity, immunomodulator, analgesic and lactagogue. However, this has not been widely socialized to postpartum mothers. The purpose of this activity is to provide education to post-partum mothers regarding plants that can increase breast milk production. The method of implementing this activity is the socialization to postpartum mothers about the benefits of the leaves of the wakes (Coleus Amboinicus Lour.) on increasing breast milk production. The result of this activity is that postpartum mothers can find out and utilize traditional plants such as the wake-up leaf (Coleus Amboinicus Lour.) and can apply it directly to increase milk production.